Edukasi Pembelajaran Biologi Berbasis Lingkungan pada Masa Pandemi Bagi Guru Biologi Di Kalimantan Barat - Setiadi, Anandita Eka; Aulia, Fitri Dayanti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The government's efforts to reduce the spread of COVID-19 have forced teachers to carry out remote learning via online. Online learning requires an attractive learning design by utilizing learning resources easily accessible to students while studying at home. Community service programs are prioritized to address high school biology learning problems in West Kalimantan during the COVID-19 pandemic, especially those related to environment-based biology learning. Community service activities were carried out on 10 - 11 June 2020. The target communities for this activity are biology teachers in West Kalimantan. The community service program is focused on environmental-based biology learning educational activities during the pandemic, which are held online through webinars with a zoom application. The activity results showed that the participants' response and enthusiasm in participating in the activity were outstanding. Participants not only asked questions but also shared experiences and information about biology learning activities during a pandemic. Through this service program, teachers are expected to be motivated to design and implement environment-based learning for innovative biology learning